2015
DOI: 10.5103/kjsb.2015.25.4.401
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Corrective Hip Joint Exercises and Foot Orthotics on RCSP, Ankle's Range of Motion, and Core Muscle Strength for Middle School Students with Pes Planus

Abstract: Objective : The purpose of this study is to evaluate the effects of hip joint exercises and orthotics on RCSP, ankle's range of motion, and core muscle strength of middle school students with pes planus. Method : Out of the original pool of 200 students, 60 students with pes planus (RCSP < -2) were selected for the study. The selected 60 students were then divided into four groups. The first group was a combined orthotics and exercise group (12 students), the second was the orthotics-only group (9 students), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…Some of these are the angulations observed in the subtalar joint as a result of the increase in loading to the medial, and thus, the pronation of the foot. The excessive pronation observed in the foot, together with pes planus, causes biomechanical changes in the ankle, knee, and hip joint [25,28]. Agoada et al [26] showed that subtalar angle was correlated with excessive pronated foot and pes planus as it can be seen in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Some of these are the angulations observed in the subtalar joint as a result of the increase in loading to the medial, and thus, the pronation of the foot. The excessive pronation observed in the foot, together with pes planus, causes biomechanical changes in the ankle, knee, and hip joint [25,28]. Agoada et al [26] showed that subtalar angle was correlated with excessive pronated foot and pes planus as it can be seen in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Feet were classified as normal if the measured value was -2° or more, or 2° or less, narrow if the angle was 3° or more, and flat if the value was -3° or less (Song et al, 1996;Valmassy, 1996;Kim, 2013). To reduce the error between researchers, the same researcher measured the RCSP of the subject's right foot repeatedly three times for either the wearing of the basic sock (S1) or the test sock (S2).…”
Section: Arch Supportmentioning
confidence: 99%